Enhancing Supply Chain Performance for Sustainable Development in the Small and Micro Industries The Role of Organizational and Local Culture, Support from Financial Institutions, and Government - Revadi, Chindy E; Armadani, Elvi; Siregar, Lina Sari (Journal of Sustainable Economics, 2025)
The economic growth potential of North Sumatra is globally recognized due to the achievement of sustainable development goals. This research aims to explore the integration of environmental, social, economic, organizational, local culture, government, and financial institution support factors that can improve supply chain performance and sustainability for small and micro industries in North Sumatra. The study uses a mixed-methods approach that involves in-depth interviews and structured questionnaires to examine the central roles of these factors. The findings underscore the importance of environmental considerations in supply chain management, the impact of local cultural traditions on organizational performance, and the need for innovative economic solutions to improve efficiency and traceability by government and financial support. The research also suggests the implementation of comprehensive policies that integrate all aspects of collaboration to achieve the Sustainable Development Goals in North Sumatra, addressing deglobalization and geopolitical crises.